2012
DOI: 10.1093/jrr/rrs059
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rectal bleeding associated with I-125 brachytherapy for prostate cancer

Abstract: The purpose of this study was to determine the risk factors for rectal bleeding after prostate brachytherapy. Between April 2005 and September 2009, 89 patients with T1c-2cN0M0 prostate cancer were treated with permanent I-125 seed implantation alone. The prostate prescription dose was 145 Gy, and the grade of rectal bleeding was scored according to the Common Terminology Criteria for Adverse Events version 4.0. Post-treatment planning was performed with fusion images of computerized tomography and magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The reported incidence of this complication is less than 0.1% [36, 37], and most cases occurred following rectal instrumentation or rectal biopsies after seed implantation [38] as occurred in our patient. This can be mitigated with the education of patients and rectal surgeons.…”
Section: Discussionmentioning
confidence: 77%
“…The reported incidence of this complication is less than 0.1% [36, 37], and most cases occurred following rectal instrumentation or rectal biopsies after seed implantation [38] as occurred in our patient. This can be mitigated with the education of patients and rectal surgeons.…”
Section: Discussionmentioning
confidence: 77%
“…The volume of rectum receiving 100% of the prescription dose (V 100 ) appears to be a reliable predictor of significant late rectal toxicity, emerging as a significant predictor in nine studies, including the two largest that reviewed dosimetric data (10,12,16,17,21,24,27,28,41). Some studies have identified other parameters, such as maximum rectal dose, as significant predictors of rectal toxicity (7,20,25,31,39).…”
Section: Predictorsmentioning
confidence: 99%
“…(17,27,31,59)) and others reporting dosimetry from CTs obtained at least a month after implantation (e.g., Refs. (7,10,12,21,39,41)). Investigators have also variably defined the rectal organ at risk as the outer rectal wall, inner rectal wall, or entire rectum as a solid structure.…”
Section: Predictorsmentioning
confidence: 99%
“…However, in the present study, no difference was observed in the use of antithrombotic therapy. The use of antithrombotic therapy also results in a rectal bleeding risk after BT or EBRT monotherapy [ 16 , 19 ]; hence, the limited number of patients in the present study was a possible reason for this difference in results compared to previous studies. In addition, ADT was performed as neoadjuvant therapy and it did not affect rectal bleeding.…”
Section: Discussionmentioning
confidence: 74%